Executorial Power of State Administrative Court Decisions Associated with General Principles of Good Government - Setiawan, Deni; Dwi Istinah, Siti Rodhiyah (Jurnal Daulat Hukum, 2023)
The purpose of this research is to find out and analyze the executorial mechanism of the State Administrative Court's decisions, to know and analyze the executive power of the State Administrative Court's Decisions associated with the General Principles of Good Governance and to find out and analyze sanctions against Administrative Officials/Bodies. State Enterprises that do not implement the decisions of the State Administrative Court. This study uses a normative juridical method with the approach used is a statute approach and a conceptual approach based on descriptive analytical research specifications. In this context it is necessary to study the executorial power of court decisions and other reasons that may be the cause of the success and failure of the implementation of decisions so that it can be seen that apart from executorial power there are other conditions that are responsible for all the successes and failures in resolving disputes at the State Administrative Court. All of this boils down to the morality of the officials concerned and laws and regulations that do not explicitly regulate the implementation of punishments/sanctions from the state administrative court (PTUN). Officials who do not carry out the obligations ordered in the decision of the State Administrative Court which has permanent legal force (inkracht van gewijsde), will be subject to moderate administrative sanctions which include: a) payment of forced money and/or compensation; b) temporary dismissal by obtaining office rights; or c) temporary dismissal without obtaining office rights.